Alternative yeasts for winemaking: Saccharomyces non-cerevisiae and its hybrids. Issue 11 (24th July 2018) - Pérez-Torrado, Roberto; Barrio, Eladio; Querol, Amparo
ABSTRACT: Wine fermentation has not significantly changed since ancient times and the most traditional aspects are seen by the market as elements that uplift wine nuances and quality. In recent years, new trends have emerged from the sector in line with consumer preferences, and due to the effects of global climate change on grape ripening. In the first cases, the consumers are looking for wines with less ethanol and fruitier aromas and in the second cases the wineries want to reduce the wine alcohol levels and/or astringency. New yeast starters of alternative Saccharomyces species and their hybrids can help to solve some problems that wineries face. In this article we review several physiological and genetic aspects of S. uvarum and S. kudriavzevii and the hybrids, which are especially relevant during the winemaking process, such as their good fermentative capabilities at low temperatures, resulting in wines with lower alcohol and higher glycerol amounts.